2006
DOI: 10.1016/j.cbd.2006.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Thermal sensitivity of uncoupling protein expression in polar and temperate fish

Abstract: Uncoupling proteins (UCP), capable of increasing proton leakage across the inner mitochondrial membrane, may play a role in the temperature-dependent setting of energy turnover in animals (and their mitochondria). Therefore, the genes and expression of fish UCP were investigated in the Antarctic eelpout Pachycara brachycephalum and a temperate confamilial species, the common eelpout Zoarces viviparus. UCP full-length cDNA was amplified from liver and muscle using RT-PCR and rapid amplification of cDNA ends (RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 51 publications
2
31
1
Order By: Relevance
“…The large populations of fish found in the nutrient-rich waters of this frozen continent possess unusual adaptations for surviving the rigors of low temperatures. In fact, Antarctic fish have evolved a number of physiological changes, including a low basal metabolic rate [1,2] and a substantial reduction in the hematocrit, which reaches its extreme in the complete loss of both red blood cells (RBCs) and hemoglobin in the Channichthyidae species [3]. Interestingly, organisms living in the oxygen-rich cold water of Antarctica have naturally high tissue oxygen concentrations, as result of their adaptations [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The large populations of fish found in the nutrient-rich waters of this frozen continent possess unusual adaptations for surviving the rigors of low temperatures. In fact, Antarctic fish have evolved a number of physiological changes, including a low basal metabolic rate [1,2] and a substantial reduction in the hematocrit, which reaches its extreme in the complete loss of both red blood cells (RBCs) and hemoglobin in the Channichthyidae species [3]. Interestingly, organisms living in the oxygen-rich cold water of Antarctica have naturally high tissue oxygen concentrations, as result of their adaptations [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Mark et al (2006b) found the mitochondrial uncoupling protein UCP2 over expressed following 2 months of cold acclimation at 2°C in the North Sea eelpout, as well as following prolonged warm acclimation to 5°C in the polar eelpout. Thus, UCP expression parallels the increased HIF activity found in the present study.…”
mentioning
confidence: 97%
“…The PCR reaction containing 1.5·mmol·l -1 MgCl 2 was performed with 32 cycles of 45·s denaturation at 94°C, 2·min annealing at 57±6°C and 1·min elongation at 72°C. Separation, cloning and analyses of PCR fragments was performed as described by Mark et al (Mark et al, 2006).…”
Section: Rna Isolation and Construction Of Probesmentioning
confidence: 99%
“…Forward primers for amplification of the 5Ј terminus and backward primers for the 3Ј terminus, corresponding to the adapter sequence, were provided with the kit. Cloning and analysis of positive clones was performed as for RT-PCR fragments (Mark et al, 2006).…”
Section: G Eckerle and Othersmentioning
confidence: 99%
See 1 more Smart Citation